Clinical implications of inflammation in atheroma formation and novel therapies in cardiovascular diseases - Barungi, Shivan; Hernández-Camarero, Pablo; Moreno-Terribas, Gerardo; Villalba-Montoro, Rafael; Marchal, Juan Antonio; López-Ruiz, Elena; Perán, Macarena (Frontiers in Cell and Developmental Biology, 2023)
Cardiovascular diseases (CVD) are the leading causes of death and disability in the world. Among all CVD, the most common is coronary artery disease (CAD). CAD results from the complications promoted by atherosclerosis, which is characterized by the accumulation of atherosclerotic plaques that limit and block the blood flow of the arteries involved in heart oxygenation. Atherosclerotic disease is usually treated by stents implantation and angioplasty, but these surgical interventions also favour thrombosis and restenosis which often lead to device failure. Hence, efficient and long-lasting therapeutic options that are easily accessible to patients are in high demand. Advanced technologies including nanotechnology or vascular tissue engineering may provide promising solutions for CVD. Moreover, advances in the understanding of the biological processes underlying atherosclerosis can lead to a significant improvement in the management of CVD and even to the development of novel efficient drugs. To note, over the last years, the observation that inflammation leads to atherosclerosis has gained interest providing a link between atheroma formation and oncogenesis. Here, we have focused on the description of the available therapy for atherosclerosis, including surgical treatment and experimental treatment, the mechanisms of atheroma formation, and possible novel therapeutic candidates such as the use of anti-inflammatory treatments to reduce CVD.